On the quasitriangular structures of abelian extensions of ℤ2. Issue 11 (3rd November 2021) - Zhou, Kun; Liu, Gongxiang
Abstract: The aim of this paper is to study quasitriangular structures on a class of semisimple Hopf algebras k G # σ, τ k Z 2 constructed through abelian extensions of k Z 2 by k G for an abelian group G . We prove that there are only two forms of them and we get a complete list of all universal R -matrices of the generalized Kac-Paljutkin algebra H 2 n 2 (see Section 2 for the definition).